2016
DOI: 10.1097/pcc.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Longer Hospital Stay Following the Fontan Operation

Abstract: In this series, 75% of patients had a postoperative length of stay less than or equal to 2 weeks. Preoperative factors suggesting worse hypoxemia/decreased pulmonary blood flow (higher hemoglobin and lower oxygen saturation) and increased pulmonary artery pressure were associated with prolonged length of stay. These findings may help risk stratify this complex patient population, provide more accurate family counseling, and provide preliminary data for changes in preoperative timing of the Fontan and/or change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
2
20
1
1
Order By: Relevance
“…This was expected as elevated pulmonary artery pressures after TCPC lead to elevated central venous pressure, increased chest tube drainage, and clinical right heart failure. 6, 20, 21 In contrast to a previous multi-center study, 8 we found no relationship between atrioventricular valve regurgitation and length of stay in our analysis. The mechanism of atrioventricular valve regurgitation is multifactorial in single ventricle patients, including, but not limited to, annular dilation from volume overload and leaflet tethering from papillary muscle displacement.…”
Section: Discussioncontrasting
confidence: 99%
“…This was expected as elevated pulmonary artery pressures after TCPC lead to elevated central venous pressure, increased chest tube drainage, and clinical right heart failure. 6, 20, 21 In contrast to a previous multi-center study, 8 we found no relationship between atrioventricular valve regurgitation and length of stay in our analysis. The mechanism of atrioventricular valve regurgitation is multifactorial in single ventricle patients, including, but not limited to, annular dilation from volume overload and leaflet tethering from papillary muscle displacement.…”
Section: Discussioncontrasting
confidence: 99%
“…Prolonged pleural and peritoneal effusions, however, remain as a significant source of morbidity after the TCPC operation. 1,2 The high pre-operative pulmonary artery pressure is a risk factor for prolonged pleural effusion. 3 Sildenafil has been used in the treatment of pulmonary hypertension.…”
mentioning
confidence: 99%
“…Prolonged length of stay was defined as length of stay greater than the 75th percentile at our institution. 21…”
Section: Definitionsmentioning
confidence: 99%